Radiographic evaluation of transverse ulna fractures treated with the intramedullary pin-external skeletal fixator (IM-ESF) tie-in technique in pigeons (Columba livia domestica) - Abu, Jalila; Wallace, Lizabeth J.; Redig, Patrick Thomas; Ogema, T. R.; Bechtold, Joan E. (Universiti Putra Malaysia Press, 2004)
Thirty five pigeons with mid-shaft transverse ulna fracture treated with intramedullary pin-external skeletal fixator (IM-ESF tie-in) technique showed healed in 94% (33 ulnas) of the cases. Only 2 ulnas (6%) showed evidence of delayed healing. Most of the fracture sites healed with secondary bone healing (84%). Primary bone healing occurred in only 3 birds (8.6%). No evidence of implant failure was found in any ulna treated with this technique.